PERILAKU MASYARAKAT DESA SEBAGAI FAKTOR RISIKO PENYAKIT HIPERTENSI - Saiful Nurhidayat (ARISTO, 2016)
Hypertension is an abnormal increase in blood pressure in the arteries continuously over a period. People with hypertension are very heterogeneous and suffered by people who come from different sub - groups at risk in the community. Hypertension is influenced by multiple risk factors, both endogenous such as age, gender and genetics / heredity, or exogenous, such as eating behavior or unhealthy diet (obesity), the behavior of salt intake, smoking and coffee drinking behavior). The purpose of this study is to get an idea of the behavior of the community as a risk factor for hypertension, and analyze the behavior of the dominant society as a risk factor for hypertension. The study was conducted in the village Slahung Ponorogo, a representative sample of 100 respondents taken by purposive sampling. Design Cross sectional quantitative design. The instrument of this study using questionnaires and observation sheets. Analysis using frequency distribution. The result showed the eating behavior or unhealthy diet (obesity) is a risk factor with the highest prevalence of hypertension with a percentage of 88% or 88 respondents. The behavior of the community as a risk factor for hypertension in sequence from the most dominant is eating behavior or unhealthy diet (obesity) a number of 88 respondents, coffee consumption behavior of a number of 77 respondents, some 66 respondents smoking behavior and excessive salt consumption behavior a number of 14 respondents. With these results it is possible the respondents have more than one behavior as a risk factor for hypertension. For that is expected to increase healthy behavior in an effort to prevent hypertension disease risk factors that can lead to complications. In addition to the sustainability of this study, the researchers will further examine the behavior of the community in preventing complications of hypertension in rural communities.Keywords : Behavior, Rural Communities, Risk Factors, Disease Hypertension.